A Study on Body Composition, Blood Pressure and Blood Sugar Levels Among Bengali Hindu and Santals Using Cultural Consonance Model. Issue 1 (June 2021) - Kanrar, Priyanka; Som, Nivedita; Roy, Subho
We examined how the perception/beliefs towards lifestyle and the actual lifestyle are related to body composition, blood pressure and blood sugar levels among Santals and Hindu caste populations using the cultural consonance model. The study involved 210 individuals (109 Bengali Hindu and 101 Santals), aged 18–50 years living in the city of Howrah, West Bengal, India. Principal component analyses were performed to extract the components from the variables used in perception towards lifestyle. Multiple linear regression analyses and multivariate analysis of covariance were used to understand association of body composition, blood pressure and blood sugar levels with both the perception towards and actual lifestyle and ethnicity, respectively. Results showed that there is a difference between perception towards and actual pattern of lifestyle among the members of two ethnic groups, indicating low cultural consonance. However, both the variables were associated with body composition, blood pressure and blood sugar levels, but not ethnicity, after removing the effects of socio-demographic and lifestyle variables. We conclude that shared knowledge and perception towards healthy lifestyle among individuals, perhaps encoded in own culture, often fail to get translated in actual lifestyle pattern and eventually affect physical health.